Increasing Brand Awareness of Sunshine Children Centre by Highlighting its Unique Selling Points in a Promotional Video - Stephanie Sutanto; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2021)
Sunshine Children Centre, Semarang is an English Course established in 2005 by Sri Mulyani Gondowardono. This course teaches students from young toddlers up until Grade 6. Sunshine Children Centre’s main problem is the decreasing number of students due to the changes from offline to online classes and the fact that this course does not have any promotional tool. Therefore, after considering many factors, the best solution is to make a promotional video and upload it to social media platforms such as Instagram. The duration of the video is only a minute as a promotional video should not last longer than two minutes (Klass, 2018). The video highlights all of the three Unique Selling Points (USPs). The first USP is that this course helps students in their homework and give additional assignments. Second, it offers courses for small groups and private students while the last USP is that it accepts students from both regular and immersion curriculum. By having an engaging promotional video, Sunshine Children Centre will expectedly be able to attract new customers and maintain existing students.Keywords: online learning, promotional video, Unique Selling Points